(untitled) (INNOVATIVE ECONOMY, 2023)
Venherska N.S., Vorona R.A. SMARTIZATION AND DECARBONIZATION OF UKRAINIAN METALLURGICAL ENTERPRISES AS DIRECTIONS OF INNOVATIVE DEVELOPMENT IN THE CONDITIONS OF EUROPEAN INTEGRATION Purpose. The purpose of the article is to reveal the features of the innovative development of metallurgical enterprises based on smartization and decarbonization in the conditions of European integration. Methodology of research. General scientific and special methods of economic research were used in the process of conducting the research, in particular: a systematic approach – for highlighting the theoretical aspects of the digital economy, the Internet of Things, eco-modernization and “green” corporate culture; analysis – to reveal the processes of digitization, smartization and decarbonization in the metallurgical industry; interdisciplinary – for considering the problem of innovative development of the metallurgical industry; abstract and logical – when making theoretical generalizations and forming conclusions. Findings. The theoretical aspects of the digital economy, the Internet of Things, eco-modernization and “green” corporate culture are highlighted. The trends of smartization and decarbonization of international and Ukrainian metallurgical enterprises are shown. The trends, problems and needs of the metallurgical industry in the conditions of European integration are highlighted. Enterprises of the metallurgical industry need eco-modernization, “greening” of production and “green” culture, finding investments for decarbonization, increasing competitiveness on an innovative basis, and adapting to the requirements of the European Green Deal. It is proposed to ensure technological development thanks to investments in smart technologies and “green” innovations through investment partnerships with EU countries and Great Britain. It is important to build an innovative HR management system and “green” corporate culture, which affects the improvement of the environmental efficiency of the enterprise. Originality. Possible directions of the metallurgical industry enterprises transformation to a new level of technological development are proposed: 1) investments in smart technologies and “green” innovations through investment partnerships with EU countries and Great Britain; 2) studying the best European practices of transition to green production, taking into account adaptation to Ukrainian conditions; 3) formation of innovative corporate culture through cultural digital transformations and “green” culture at enterprises. Practical value. The proposed recommendations can be used for the strategic directions improvement of metallurgical enterprises development in the conditions of smartization and decarbonization of production. Key words: metallurgical enterprise, smartization, decarbonization, innovative corporate culture, green values, European integration.